Study of the presence and environmental risk of organic contaminants policed by the European Union and other organic compounds in the water resources of a region overlapping protected areas: The Guadiaro River basin (southern Spain) - Llamas Dios, Marta Inés; Fernández-Valenzuela, P.J.; Vadillo-Pérez, Iñaki; Sanmiguel-Martí, M.; Rambla-Nebot, J.; Rambla-Nebot, J.; Jiménez-Gavilán, Pablo (Elsevier, 2023)
The study presented here is a first qualitative assessment of the occurrence of organic contaminants contemplated and not yet contemplated in European Union environmental legislation in water resources in the little anthropized Guadiaro River basin (70% of its area is covered by natural vegetation), in southern Spain. Water samples were collected from four carbonate aquifers, two detrital aquifers and four surface water courses and were analyzed for (i) 171 organic contaminants, (ii) major ions and (iii) stable isotopes (δ18OH2O, δ2HH2O, δ13CDIC). An environmental risk assessment was conducted through calculation of risk quotients comparing measured concentrations with ecotoxicological data found in the literature. Twenty-five organic contaminants were detected, at least once, including pesticides, pharmaceuticals, drugs of abuse and polycyclic aromatic hydrocarbons (PAHs). Cocaine and its main metabolite were detected in 85% and 95% of water samples, respectively (0.001–0.18 μg/L and 0.004–0.6 μg/L, respectively). Pyrene (PAH) was found in all water samples (0.001–0.015 μg/L) and forest fires were pointed out as a potential diffuse source. Relationship between rivers and aquifers is reflected by the distribution of organic contaminants, essentially the drugs of abuse. Concentration of contaminants were generally higher in groundwater samples, especially from detrital aquifers, potentially due to an accumulation process promoted by irrigation-return flows and by its slow dynamic compared to that of karstic systems. Pyrene concentration was also higher in some springs from karstic aquifers. Hence, calculated risk quotients were in general higher in groundwater, meaning that the threat to surface aquatic systems can grow as aquifers increase their influence on the water courses as the dry season progresses. The relationship between δ13CDIC and most organic contaminants (especially pyrene) reveal the role of the soil as storage media.
Keywords: Contaminantes; Agua -- Contaminación; Aguas subterráneas -- Contaminación; Capa freática; Contaminación -- Evaluación del riesgo; Acuíferos; España meridional; Emerging contaminants; Groundwater; Surface water; Risk assessment; Aquifer pollution; Southern Spain